2022
DOI: 10.15441/ceem.22.324
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of vasopressor requirement among hypotensive patients with suspected infection: usefulness of diastolic shock index and lactate

Abstract: Objective We evaluated the performance of diastolic shock index (DSI) and lactate in predicting vasopressor requirement among hypotensive patients with suspected infection in an emergency department.Methods This was a single-center, retrospective observational study for adult patients with suspected infection and hypotension in the emergency department from 2018 to 2019. The study population was split into derivation and validation cohorts (70/30). We derived a simple risk score to predict vasopressor requirem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…In a similar way, a recent retrospective study showed that DSI and lactate values identified patients who were more likely to require a vasopressor in the context of hypotension and suspected infection. 8 Even though these results are in line with previous reports, 7 the usefulness of DSI in clinical practice has not yet been demonstrated.…”
supporting
confidence: 53%
See 3 more Smart Citations
“…In a similar way, a recent retrospective study showed that DSI and lactate values identified patients who were more likely to require a vasopressor in the context of hypotension and suspected infection. 8 Even though these results are in line with previous reports, 7 the usefulness of DSI in clinical practice has not yet been demonstrated.…”
supporting
confidence: 53%
“…The patients subjected to very early vasopressor use in that cohort received a lower volume of resuscitation fluids, exhibited less net fluid accumulation, and had shorter hypotension times [ 9 ]. Similarly, in a recently published study, patients with simultaneous increases in their lactate and DSI levels had a lower 28-day mortality risk when vasopressors were initiated very early [ 8 ]. In contrast, others have reported opposite results when vasopressors were introduced very early during the resuscitation process [ 10 ], although it is not clear that this difference indicated an effect of the early start of vasopressors or simply reflected the presence of a more severe disease condition.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…Previously, vasopressor requirement prediction models were developed using the Acute Physiology and Chronic Health Evaluation III score, lactate level, acute kidney injury, intravenous crystalloid administration, and hypotension (<90 mm Hg) (30–32). To achieve a higher predictive performance, models usually select many components that require resources, including time and healthcare providers.…”
Section: Discussionmentioning
confidence: 99%